2001
DOI: 10.1051/fruits:2001133
|View full text |Cite
|
Sign up to set email alerts
|

Effect of some growth regulators on some fruit characteristics and productivity of the Barhee date palm tree cultivar (Phoenix dactyliferaL.)

Abstract: Effect of some growth regulators on some fruit characteristics and productivity of the Barhee date palm tree cultivar (Phoenix dactylifera L.).Abstract -Introduction. The date palm tree is one of the fruit trees most cultivated in the Arabian Gulf States. Bioregulators were used for the quality and productivity improvement of date palm tree fruits. A study was conducted to assess the relative effectiveness of GA 3 , NAA, ethephon and a mixture of growth regulators on some fruit characteristics and productivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 6 publications
1
14
0
2
Order By: Relevance
“…The increase in bunch weight might be due an increase in fruit weight of date palm. The results are further supported by Shabana et al, (1976); Shabana et al (1998); Aljuburi et al, (2001); Aljuburi et al, (2003); Aboutalebi and Beharoznam, (2006) [18][19][20][21][22] who applied NAA at concentration of 150 and 200 ppm and found a significant increase in bunch weight of different date palm cultivars. Conclusion.…”
Section: Source Of Variationsupporting
confidence: 59%
“…The increase in bunch weight might be due an increase in fruit weight of date palm. The results are further supported by Shabana et al, (1976); Shabana et al (1998); Aljuburi et al, (2001); Aljuburi et al, (2003); Aboutalebi and Beharoznam, (2006) [18][19][20][21][22] who applied NAA at concentration of 150 and 200 ppm and found a significant increase in bunch weight of different date palm cultivars. Conclusion.…”
Section: Source Of Variationsupporting
confidence: 59%
“…Also, the application of NAA at (40 and 60) mg·L -1 on 'Zahdi' dates at the late kimri stage increased fruit size and delayed ripening by one month [16]. Al-Juburi et al reported that NAA or a mixture of growth regulators (NAA, GA 3 and ethephone) application on 'Khenazi' dates, 20 days following pollination, delayed fruit ripening [18]. Also, the application of benzyladenine (BA) and other cytokinines effectively delayed ripening of apples and other fruits [19].…”
Section: Discussionmentioning
confidence: 99%
“…The application of NAA at (50 and 100) mg·L -1 on 'Sewy' dates at 10-30 days following the fruit set stage increased fruit drop and decreased yield but improved fruit weight and quality compared with control [17]. The application of NAA or a mixture of growth regulators (NAA, GA 3 and ethephone) on 'Khenazi' dates at 20 days following pollination delayed fruit ripening for one month, decreased dry matter, and increased fruit weight and yield per tree [18]. Also, the application of benzyladenine (BA) and other cytokinines effectively delayed ripening of apples and other fruits [19].…”
Section: Introductionmentioning
confidence: 99%
“…Os caules múltiplos formam touceiras, que normalmente alcançam 4,5 m de altura e 2 a 3 cm de diâmetro e são cobertos por fibras emaranhadas (LORENZI, 1996). Desenvolve-se melhor em situação de leve sombreamento e apresenta coloração amarelada quando cultivada em pleno sol, na fase jovem (BLOSSFELD, 1965). Essa tolerância ao sombreamento é uma das características que faz que a espécie predomine na decoração de casas e escritórios.…”
Section: Introductionunclassified
“…Estudos sobre a aplicação de ácido giberélico em palmeiras vêm sendo realizados visando acelerar a germinação de sementes (BROSCHAT e DONSELMAN, 1988;MORA-AGUILAR et al, 2003), aumentar o florescimento e frutificação (EL-HODAIRI et al, 1992;ALJUBURI et al, 2001) e cultivo in vitro (SAMYN, 1993).…”
Section: Introductionunclassified